Lengua 7 Prácticas de lectura y escritura - GUIDO, María Rita coord. (ESTRADA, 2000)
CONTENIDO : BLANCO, MARIA IMELDA; GROPPO, MARCELA; LAERA, ALEJANDRA; MATEO, SILVIA; PALERMO, ALEJANDRO; ANSOLABEHERE, PABLO JAVIER